Human-pathogenic Anaplasma spp., and Rickettsia spp. in animals in Xi'an, China. - Wen-Ping Guo; Baicheng Huang; Qin Zhao; Gang Xu; Baoyuan Liu; Yi-Han Wang; En-Min Zhou (PLOS Neglected Tropical Diseases, 2018)
In China, thirteen species of tick-borne rickettsiales bacteria pathogenic to human have been reported in ticks and host animals, and human patients caused by them also has been identified. However, investigation for rickettsiales bacteria circulating in Xi'an wasn't performed although diseases resembling human diseases caused by these organisms have been found. In this study, domestic animals and ticks in Xi'an, China, were tested for the presence of rickettsiales bacteria pathogenic to humans. Besides A. ovis, a high prevalence of A. capra was observed suggesting a high public health risk exists. In addition, two novel Anaplasma species closely related to A. phagocytophilum were identified and formed distinct lineages in the phylogenetic trees, with more than 98.3% identities for rrs gene, while divergences up to 20.2% and 37.0% for groEL and gltA genes, respectively. Both of these two novel Anaplasma species were found to circulate in goats and further assessment of their pathogenicity is needed. Ca. R. jingxinensis, with potential pathogenicity, was also detected in H. longicomis ticks with high prevalence. However, other causative agents were not identified although they were distributed in other areas of China.